Application of a borate-containing glass for the treatment of trophic wounds in children, suffering myelodysplasia - М. G. Меlnychenko; І. R. Dilanyan; L. P. Маtviychuk; А. М. Кlymenko (Клінічна хірургія, 2019)
Objective. To estimate the possibility of application of a borate-containing glass material while treating trophic wounds in children, suffering myelodysplasia.